2012
DOI: 10.1002/aoc.1866
|View full text |Cite
|
Sign up to set email alerts
|

Ru(II) complexes bearing tertiary phosphine ligands: a novel and efficient homogeneous catalyst for one‐pot synthesis of dihydropyrano[3,2‐c]chromene and tetrahydrobenzo[b]pyran derivatives

Abstract: A number of ruthenium complexes were prepared and their catalytic activities in three-component one-pot condensation of aldehydes, malononitrile and 4-hydroxycoumarin or dimedone was considered to afford dihydropyrano[3,2-c]chromenes and tetrahydrobenzo [b]pyran derivatives under optimum reaction conditions. We found that a catalytic amount of RuBr 2 (PPh 3 ) 4 efficiently promotes the reaction in a short time (3-15 min) and with high yield (75-88%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…To reveal the advantages of this catalyst, its catalytic activity in the model reaction involving benzaldehyde, malononitrile and 4‐hydroxycoumarin was compared with those of previously reported systems (Table ). As evident from Table , the catalytic activity of Ag 3 PMo 12 O 40 was compared with other catalysts such as [DMAP‐PEG 1000 ‐DI L][BF 4 ], nano‐ZnO, crown ether complex cation ionic liquids (CECILs), ammonium acetate, titanium dioxide nanowires, nanomagnetic double‐charged diazoniabicyclo[2.2.2]octane dichloride silica hybrid (Fe 3 O 4 @SiO 2 /DABCO), surfactant‐modified bentonite (CTMAB‐bentonite), hexamethylenetetramine, SiO 2 /H 3 PW 12 O 40 nanohybrid, RuBr 2 (PPh 3 ) 4 , sodium malonate, NaCl, (NH 4 ) 42 [MoVI 72 MoV 60 O 372 (CH 3 COO) 30 (H 2 O) 72 ], a Keplerate‐type giant‐ball nanoporous isopolyoxomolybdate, silica‐supported molybdic acid, KNaC 4 H 4 O 6 ⋅4H 2 O (potassium sodium tartrate) and polypyrrole/Fe 3 O 4 /CNT that were previously used as catalysts in the same reaction. The results showed that compared to the other catalysts, our designed catalyst can catalyse the reaction in an appropriate manner.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To reveal the advantages of this catalyst, its catalytic activity in the model reaction involving benzaldehyde, malononitrile and 4‐hydroxycoumarin was compared with those of previously reported systems (Table ). As evident from Table , the catalytic activity of Ag 3 PMo 12 O 40 was compared with other catalysts such as [DMAP‐PEG 1000 ‐DI L][BF 4 ], nano‐ZnO, crown ether complex cation ionic liquids (CECILs), ammonium acetate, titanium dioxide nanowires, nanomagnetic double‐charged diazoniabicyclo[2.2.2]octane dichloride silica hybrid (Fe 3 O 4 @SiO 2 /DABCO), surfactant‐modified bentonite (CTMAB‐bentonite), hexamethylenetetramine, SiO 2 /H 3 PW 12 O 40 nanohybrid, RuBr 2 (PPh 3 ) 4 , sodium malonate, NaCl, (NH 4 ) 42 [MoVI 72 MoV 60 O 372 (CH 3 COO) 30 (H 2 O) 72 ], a Keplerate‐type giant‐ball nanoporous isopolyoxomolybdate, silica‐supported molybdic acid, KNaC 4 H 4 O 6 ⋅4H 2 O (potassium sodium tartrate) and polypyrrole/Fe 3 O 4 /CNT that were previously used as catalysts in the same reaction. The results showed that compared to the other catalysts, our designed catalyst can catalyse the reaction in an appropriate manner.…”
Section: Resultsmentioning
confidence: 99%
“…1 H NMR (300 MHz, DMSO‐ d 6 ): 4.53 (s, 1H, CH), 7.33 (d, J = 6.0 Hz, 2H), 7.48–7.55 (m, 4H, NH 2 ), 7.75 (dt, J = 7.8,1.2 Hz, 1H); 7.92 (dd, J = 7.8,1.2 Hz, 1H); 8.52 (d, J = 6.0 Hz, 2H). 13 C NMR (75 MHz, DMSO‐ d 6 , δ , ppm): 36.9, 56.9, 103.0, 113.4, 117.1, 119.4, 123.0, 123.4, 125.5, 133.6, 150.2, 152.2, 152.8, 154.6, 158.6, 160.1 6‐Amino‐3‐methyl‐4‐phenyl‐1,4‐dihydropyrano[2,3‐ c ]pyrazole‐5‐carbonitrile ( 4f ): FT‐IR (KBr, ν max , cm −1 ): 3450, 3370, 2195, 1645, 1610, 1605, 1446.…”
Section: Methodsmentioning
confidence: 99%
“…In general, 3,4‐dihydropyrano[3,2 c]chromenes are accessible through the one‐pot three‐component condensation of an aromatic aldehyde, malononitrile, and 4‐hydroxycoumarin. Several synthesis of these heterocyclic compounds have been reported, using various catalysts like synthetic diammonium hydrogen phosphate (DAHP), Tetrabutylammonium bromide (TBAB), Sodium dodecyl sulfate (SDS), 4‐(dimethylamino) pyridine (DMAP), [ 14 ] poly(N,N′‐dibromo‐N‐ethyl‐benzene‐1,3‐disulfonamide) [PBBS], ionic liquid [DBU][AC], [ 15 ] Silica‐Grafted Ionic Liquids[Sipim]HSO 4, starch solution, thiourea dioxide, poly (ethylene glycol) grafted N,N‐dimethylaminopyridine functionalized dicationic ionic liquid [DMAP‐PEG1000‐DIL][BF 4 ], 1‐Methylimidazolium tricyanomethanide ([HMIM]C(CN) 3 ) and Ru(II) complexes bearing tertiary phosphine ligands . Despite this, these procedures have drawbacks, which imply unsatisfactory yields, extended reaction times and the use of expensive catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of various 3,4-dihydropyrano[c]chromene derivatives have been reported using catalysts such as K2CO3 [17],tetrabuthylammonium bromide (TBAB) [18], s-proline [19], nano Al2O3 [20], cesium carbonate [21], thiourea dioxide [22], [DBU][Ac] [23], nano-structured ZnO [24], LSMO [25], HEAA [26], SuSa [27], [Bmim]HSO4 [28], Amberlite A21 [29], Ru(II) [30], Mo132 [31], ammonium acetate [32], DBU [33], piperidine [34], NaBr [35], ([DMAP-PEG1000-DIL] [BF4]) [36] and ionic liquid [37].…”
Section: Introductionmentioning
confidence: 99%